2003
DOI: 10.1055/s-2003-39717
|View full text |Cite
|
Sign up to set email alerts
|

Torilin fromTorilis japonica,as a New Inhibitor of Testosterone 5α-Reductase

Abstract: The methanolic extract of the fruits of Torilis japonica showed a potent inhibition against 5 alpha-reductase activity in vitro. Bioassay-guided fractionation of the methanol extract of the fruits followed by repeated silica gel chromatography led to the isolation of an active principle and its structure was identified as torilin on the basis of spectroscopic data. Torilin (IC50 = 31.7 +/- 4.23 microM) showed a stronger inhibition of 5 alpha-reductase than alpha-linolenic acid (IC50 = 160.3 +/- 24.62 microM) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this study, avicequinone C showed its 5α-R1 inhibitory activity, with an IC 50 value of 38.8 ± 1.29 µM. Although this value indicates moderate potency, it is still better than or equivalent to the reported IC 50 values of many natural products isolated from plants, for example, the IC 50 values of 112 µM for soyasaponin1 from Pueraria thomsonii [20], 85 µM for artocarpin from Artocarpus incises [35], 40 µM for emodin from Polygonum multiflorum Thunb [36], 31.7 µM for triolin from Torillis japonica [37], 390 µM, 230 µM, 220 µM and 220 µM for 1,7-diphenylhept-4-en-3-one, dihydroyashabushiketol, 5-hydroxy-7-(4''-hydroxy-3''-methoxyphenyl)-1-phenyl-3-heptanone and 5-hydroxy-7-(4''-hydroxyphenyl)-1-phenyl-3-heptanone from Alpinia officinarum [38] and 44 µM, 103 µM and 48 µM for (‒)-cubebin, (‒)-3,4-dimethoxy-3,4-desmethylenedioxycubebin and piperine from Piper nigrum , respectively [39].…”
Section: Resultsmentioning
confidence: 89%
“…In this study, avicequinone C showed its 5α-R1 inhibitory activity, with an IC 50 value of 38.8 ± 1.29 µM. Although this value indicates moderate potency, it is still better than or equivalent to the reported IC 50 values of many natural products isolated from plants, for example, the IC 50 values of 112 µM for soyasaponin1 from Pueraria thomsonii [20], 85 µM for artocarpin from Artocarpus incises [35], 40 µM for emodin from Polygonum multiflorum Thunb [36], 31.7 µM for triolin from Torillis japonica [37], 390 µM, 230 µM, 220 µM and 220 µM for 1,7-diphenylhept-4-en-3-one, dihydroyashabushiketol, 5-hydroxy-7-(4''-hydroxy-3''-methoxyphenyl)-1-phenyl-3-heptanone and 5-hydroxy-7-(4''-hydroxyphenyl)-1-phenyl-3-heptanone from Alpinia officinarum [38] and 44 µM, 103 µM and 48 µM for (‒)-cubebin, (‒)-3,4-dimethoxy-3,4-desmethylenedioxycubebin and piperine from Piper nigrum , respectively [39].…”
Section: Resultsmentioning
confidence: 89%